The dress: Theme and self-presentation in online Australian wedding planning fora. (February 2020) - Laskey, Brenda; Stirling, Lesley
This investigation of the discourse of Australian women in the 'new media' context of online special interest advice fora contributes to theory about the ways in which language encodes cultural practices and mediates the social construction of identity. The linguistic self-presentation of participants in 588 asynchronous written posts to wedding planning fora was analysed. Prevalent themes were identified inductively and the degree to which each identified theme was evident in the data was measured. The study uncovered ways in which group membership criteria were expressed and found that traditional ideals of feminine perfection were reinforced. A focus of the investigation was the ways in which the participants spoke about the wedding dress. At times, it was referred to using personification as though it were a proxy for a lover. On other occasions, it appeared to function as a representation of the writer's idealized bridal self. It emerged as a highly significant cultural object which conferred a special but temporary identity.